How to improve Norway's Transport-Infrastructure Investment - Hemmings, Philip (OECD Economics Department Working Papers, 2018)
Norway makes substantial public investment in transport and this has intensified in recent years. There is potentially large economic benefit from such investment, particularly as good transport infrastructure can help Norway's transition away from oil-related activities. However, realising these gains requires sound processes for selecting and delivering projects. This paper assesses the investment process from initial proposals through evaluation, discussion, selection, approval, implementation, and ex post evaluation. It finds that, although the policy process at each stage is clear, and the planning framework has central oversight, final choices of project are often sub-optimal. The paper identifies a need for stronger top-down influence in the planning process and more influence of economic-efficiency considerations in project selection. It also calls for efforts to broaden ex post assessment of transport investment projects and reduction in project delays